A review on fundamental advancements of black hole algorithm - Zuwairie, Ibrahim; Suad Khairi, Mohammed; Norazian, Subari; Nor Azlina, Ab Aziz; Nor Hidayati, Abdul Aziz; Tasiransurini, Ab Rahman; Asrul, Adam; Zulkifli, Md. Yusof; Mohd Ibrahim, Shapiai; Norrima, Mokhtar (2018)
In recent years, there is a growing interest in the design and development of nature-inspired optimization algorithms. One of the algorithms is black hole algorithm (BHA), which is inspired by the black hole in general relativity and cosmology. This paper reports a review of the BHA. This review emphasizes on the fundamental advancements of BHA. A brief research gap is presented at the end of this paper.